Reviewing trends and the impact of immersive virtual reality on education: A bibliometric study - Nor Hannani Izzati, Abdullah; Phon, Danakorn Nincarean Eh; Nor Saradatul Akmar, Zulkifli; Mohd Faizal, Ab Razak (Politeknik Negeri Padang, 2025)
Immersive Virtual Reality (IVR) is revolutionizing education by offering immersive, interactive learning experiences that make complex subjects more accessible. This study conducts a bibliometric analysis of IVR in education from 2014 to 2024, focusing on research disciplines, keyword frequency, and highly cited articles. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach and data from Scopus, 2,183 English-language documents were analyzed to identify major research trends and influential contributions. Findings indicate that Computer Science (30.3%), Social Sciences (17.5%), and Engineering (17.2%) are the leading disciplines in IVR study, reflecting its multidisciplinary nature. Frequently occurring keywords such as “virtual reality” (2,160 occurrences) and “e-learning” (876 occurrences) highlight the integration of IVR into modern education. Additionally, highly cited articles from journals such as Computers & Education and Learning and Instruction demonstrate the growing impact of IVR studies, underscoring its effects on engagement, skill development, and instructional design. The study also highlights challenges related to access, affordability, and implementation of frameworks. Its primary contribution is to map the evolution and impact of IVR research in education, offering insight into its shift from emerging technology to a central component of immersive learning. This analysis provides a foundation for future research and policy, supporting more effective and inclusive integration of IVR in diverse educational environments by identifying disciplinary intersections and high-impact contributions.